2019
DOI: 10.1002/nop2.344
|View full text |Cite
|
Sign up to set email alerts
|

Silent voices: Family caregivers' narratives of involvement in palliative care

Abstract: AimTo explore how family caregivers experience involvement in palliative care.DesignA qualitative design with a narrative approach was used.MethodsPurposive sampling and narrative interviews were conducted. Eleven bereaved family caregivers for patients with cancer receiving palliative care were interviewed in Mid‐Norway between November 2016–May 2017.ResultsWe identified four themes related to family caregivers' experiences of involvement in the early, middle, terminal and bereavement phases of palliative car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(76 citation statements)
references
References 42 publications
3
65
1
Order By: Relevance
“…Nurses were recruited face‐to‐face by contact persons in the municipalities. A question route with open‐ended questions was developed based on the study aim and earlier research (Crawford et al, 2014; Krueger & Casey, 2015; Tarberg et al, 2019). The questions were related to how nurses had experienced compassionate care in different phases of the palliative pathway: namely the first, the second and the third phase.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Nurses were recruited face‐to‐face by contact persons in the municipalities. A question route with open‐ended questions was developed based on the study aim and earlier research (Crawford et al, 2014; Krueger & Casey, 2015; Tarberg et al, 2019). The questions were related to how nurses had experienced compassionate care in different phases of the palliative pathway: namely the first, the second and the third phase.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we followed a broad description of compassion as involving an awareness of, or a sensitivity to, the pain or suffering of others that results in taking verbal, nonverbal or physical action to remove, reduce or alleviate the impact of such affliction (Gilbert, 2013). This description is relevant because research has shown that patients and their family caregivers experience deficiencies in palliative care provision (McEwen et al, 2018; Røen et al, 2018; Tarberg et al, 2019). A Norwegian study found that family caregivers experienced limited involvement, a lack of preparation for the dying phase, and unsystematic follow‐up after death (Tarberg et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in Norway, there is a lack of research on medical staff visits to dying patients and a lack of preparation for dying. 40 Future education on the end-of-life process and communication within the team should aim to improve understanding of caregivers' needs for more guidance. 41 Caregivers should receive emotional support, companionship, and practical help through coaching and training (such as deep breathing or resting).…”
Section: Discussionmentioning
confidence: 99%